Financial Performance Analysis During and After the Covid-19 Pandemic At Garuda Indonesia Company. - Islahiyatul Asroriyah (Kampus 5 Universitas Negeri Surabaya, 2025)
This study aims to analyze in deh the financial performance of Garuda Indonesia before, during, and after the Covid-19 pandemic by using financial ratios as the main measuring tool. The research method used is a quantitative descriive analysis of financial ratios including liquidity ratios, solvency, profitability, and activities to obtain a comprehensive picture of the 's financial condition. The data used in this study is in the form of the 's annual financial statements from the period 2018 to 2023. The results of the analysis show that Garuda Indonesia financial performance from 2018 to 2023 experienced a sharp decline during the COVID-19 pandemic, namely in 2020 and 2021. The pandemic caused great pressure on the aspects of liquidity, solvency, and profitability. However, as of 2022, there are signs of recovery with gradual improvements in almost all ratios, although not yet fully stable. With this research, this study provides a comprehensive overview of how . Garuda Indonesia, is slowly recovering after facing financial challenges caused by the COVID-19 pandemic.